Investigation of Fluid Characteristic and Performance of an Ejector by a Wet Steam Model - Chen Wang; Lei Wang (Entropy, 2022)
In this paper, a wet steam model is utilized to study the fluid characteristic and performance of a supersonic ejector. The condensation process, which has been ignored by most researchers, is analyzed in detail. It is found that the most intensive condensation happens at the primary nozzle downstream and nozzle exit region. Moreover, the impacts of primary flow pressure and back pressure on ejector performance are studied by the distribution of Mach number inside the ejector. Furthermore, the results show that the secondary mass flow rate first grows sightly then remains almost unchanged, while the primary mass flow rate rises sharply and ejector entrainment ratio drops dramatically with the increase in primary flow pressure.